A role for virtual outcrop models in blended learning – improved 3D thinking and positive perceptions of learning - C. E. Bond (Geoscience Communication, 2021)
Virtual outcrop models are increasingly used in geoscience education to supplement field-based learning but their efficacy for teaching key 3D spatial thinking skills has been little tested. With the rapid increase in online digital learning resources and blended learning, most recently because of the global COVID-19 pandemic, understanding the role of virtual field environments in supporting and developing skills conventionally taught through field-based teaching has never been more critical. Here we show the efficacy of virtual outcrop models in improving 3D spatial thinking and provide evidence for positive perceptions amongst participants using virtual outcrops in teaching and learning. Our results show that, in a simple, multiple-choice scenario, participants were more likely to choose the 3D block diagram that best represents the structure when using a virtual outcrop (59 %) compared to more traditional representations, such as a geological map (50 %) or field photograph (40 %). We add depth to these results by capturing the perceptions of a cohort of students, within our full participant set, on the use of virtual outcrops for teaching and learning, after accessing a virtual field site and outcrops which they had previously visited during a day's field teaching. We also asked all participants if and how virtual outcrops could be used effectively for teaching and training, recording 87 % of positive responses. However, only 2 % of participants felt that virtual outcrops could potentially replace in-field teaching. We note that these positive findings signal significant potential for the effective use of virtual outcrops in a blended learning environment and for breaking barriers to increase the equality, diversity and inclusivity of geoscience field skills and teaching.